PROFESIONALISME APARATUR PEMERINTAH KOTA YOGYAKARTA (STUDI KASUS KANTOR CATATAN SIPIL) - Rendy Sueztra Canaldhy (UNIVERSITAS INDO GLOBAL MANDIRI, 2019)
This study, entitled Professionalism Apparatus Yogyakarta City Government (Civil Registry Office case studies). This study aims to understand / know the professionalism apparatus Civil Registry Office of Yogyakarta as well as factors inhibiting professionalism. This research was conducted at the Civil Registry Office of Yogyakarta and data collection is done by using observation and interviews with officials Civil Registry office. Professionalism public bureaucratic apparatus is closely associated with penyelenggaraaan good governance and for anyone who is dealing with the bureaucracy. Examine the importance of professionalism because the bureaucratic apparatus bureaucratic apparatus does not understand the needs of society and technological progress even tend not responsive, innovative and be indifferent service delivery publkc. This study found a pathology that has been ingrained in the self apparatus in organizing tasks and functions of the organization. Pathologies such as red tape, extortion, waiting for instructions employers, and others. The main factors that hinder the professionalism of public bureaucratic apparatus, namely the existence of formal rules rigidly regulate the roles and duties of each section so that the apparatus in performing the duties and functions of the organization are not oriented to the organization's mission but are more likely to formal rules and instructions of superiors. Keywords : Professionalism apparatus, good governance, Public service